Antiseptic property screening for 18 natural plants and efficiency-toxicity research of Coptis chinensis fermentation - Fang ZHAO; Yan WANG; Yongyan PEI; Jun SHI; Ping ZHAO; Limin ZHAO (KeAi Communications Co., Ltd., 2022)
[Abstract]: Objective: This study aimed to compare the antibacterial performance of 18 natural plants against six types of microorganisms that tend to grow in cosmetics and select the best natural antiseptic herbs with low toxicity and a broad antibacterial spectrum. The safety performance and effects of the antioxidant, whitening, and reduced inflammation of Coptis chinensis fermentation were explored. Methods: The inhibition performance of the alcoholic extracts for the 18 natural plants against six microorganisms was compared by using the cylinder plate method. The MTT assay was used to determine the cell viability of C. chinensis extract and fermentation products. DPPH, hydroxyl, and ABTS radical scavenging rates as well as iron reduction ability were used to evaluate the antioxidant efficacy. In addition, the activity inhibition rate of tyrosinase and hyaluronidase indicated the whitening and anti-inflammatory properties of C. chinensis extract and fermentation broth. Results: Results showed that among the 18 natural plants, C. chinensis extract had the most prominent inhibition circles and the smallest minimum inhibitory concentration (MIC) value against six microorganisms. After fermentation, the IC50 value of C. chinensis alcoholic extract increased significantly with the cell survival rate, indicating its low biosafety. The free radical scavenging rate, tyrosinase inhibition rate, and hyaluronidase inhibition rate of fermented C. chinensis extract increased significantly, showing better antioxidant activity, whitening activity, and anti-inflammatory activity than alcohol extract. Conclusion: Among the 18 natural plants, C. chinensis has the most substantial antibacterial ability. After fermentation by yeast, the cytotoxicity of C. chinensis decreases, and the antioxidant, whitening, and anti-inflammatory activities increase, indicating that microbial fermentation attenuates toxicity and enhances the effect of plant preservatives.